PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBALAJARAN IPAS MENGGUNAKAN MODEL KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) BERBANTUAN MEDIA SMART BOX DI KELAS IV SD - Nur Halijah Harahap; Hana Shilfia Iraqi; hamimah; Zuryanty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of fourth-grade students in Natural and Social Sciences (IPAS) learning at SDN 22 Lubuk Begalung, Padang City. The learning process was still teacher-centered, students were less active in classroom activities, collaboration among students had not been optimal, and the use of instructional media was limited, resulting in low student learning outcomes. This study aimed to describe the improvement of students' learning outcomes through the implementation of the Student Teams Achievement Division (STAD) cooperative learning model assisted by Smart Box media in IPAS learning. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model consisting of planning, action, observation, and reflection. The study was conducted in two cycles involving 23 fourth-grade students of SDN 22 Lubuk Begalung, Padang City. Data were collected through teacher and student observation sheets, learning achievement tests, and documentation. The data were analyzed qualitatively and quantitatively. The findings revealed that the implementation of the STAD cooperative learning model assisted by Smart Box media improved both the learning process and students' learning outcomes. Improvements were observed in teacher performance, student participation, and learning achievement from Cycle I to Cycle II. Classical learning mastery also reached the predetermined success criteria. Therefore, the STAD cooperative learning model assisted by Smart Box media is effective in improving elementary school students' learning outcomes in IPAS learning.